IN SILICO STUDY OF SOME FLAVONOID COMPOUNDS AGAINST ACE-2 RECEPTORS AS ANTI-COVID-19 - MUSFIROH, IDA; SIGALINGGING, OKTAVIA SABETTA; SUHANDI, CECEP; KHAIRUL IKRAM, NUR KUSAIRA; MEGANTARA, SANDRA; MUCHTARIDI, MUCHTARIDI (International Journal of Applied Pharmaceutics, 2023)
Objective: The coronavirus disease 2019 (COVID-19) pandemic has become a global concern today. As a receptor that plays an important role in viral entry, inhibition of angiotensin-converting enzyme-2 (ACE-2) activity could prevent severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Quercetin is one of the flavonoid compounds reported to have activity as an ACE-2 inhibitor via interaction with the hydroxyl group at ring B positions 3' and 4'. The aims of this research to analyze the binding interaction of some flavonoid compounds into ACE-2 receptor to predict their activity as an anticovid-19. Methods: An in silico approach via molecular docking simulations was conducted, and the selection of potential compounds was based on Lipinski's rules, prediction of absorption, distribution, metabolism, and toxicity (ADMET). Results: The results showed that nepetin was the most potent compound, with a bond energy of-4.71 kcal/mol and an inhibition constant of 355.62 µM. The compound is bound to amino acid residues Asp30, His34, Glu35, and Thr27, which are important amino acid residues of the ACE-2 receptor. Conclusion: The nepetin compound complies with all Lipinski rules and has a better ADMET profile compared to other compounds.